2019
DOI: 10.3389/fphar.2019.00045
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of lncRNA NR_046683 Serves as a Prognostic Biomarker and Potential Drug Target for Multiple Myeloma

Abstract: Aim: To investigate the prognostic value of lncRNA NR_046683 in multiple myeloma (MM).Methods: High-throughput lncRNA array was combined with bioinformatics techniques to screen differentially expressed lncRNA in MM. qRT-PCR was adopted to determine the expression of target lncRNAs in MM patients and controls.Results: It was found for the first time that lncRNA NR_046683 is closely related to the prognosis of MM. It was also detected in tumor cell lines KM3, U266, especially in drug-resistant cell lines KM3/BT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The aberrant expression of urothelial cancer associated 1 lncRNA affords it the ability to promote proliferation and inhibits apoptosis by regulating miR-1271-5p and hepatocyte growth factor in MM cells ( Yang and Chen, 2019 ). Abnormally expressed lncRNA NR_046683 in patients of different MM subtypes and stages indicated that it could be used as a new indicator for potential drug target and prognosis ( Dong et al, 2019 ). Although several lncRNA prognostic models have been identified in uterine corpus endometrial carcinoma ( Ouyang et al, 2019 ), hepatocellular carcinoma ( Sun et al, 2019b ), cervical cancer ( Wu et al, 2019 ), and lung adenocarcinoma ( Zhou et al, 2019 ), the clinical implication of most lncRNAs in MM remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The aberrant expression of urothelial cancer associated 1 lncRNA affords it the ability to promote proliferation and inhibits apoptosis by regulating miR-1271-5p and hepatocyte growth factor in MM cells ( Yang and Chen, 2019 ). Abnormally expressed lncRNA NR_046683 in patients of different MM subtypes and stages indicated that it could be used as a new indicator for potential drug target and prognosis ( Dong et al, 2019 ). Although several lncRNA prognostic models have been identified in uterine corpus endometrial carcinoma ( Ouyang et al, 2019 ), hepatocellular carcinoma ( Sun et al, 2019b ), cervical cancer ( Wu et al, 2019 ), and lung adenocarcinoma ( Zhou et al, 2019 ), the clinical implication of most lncRNAs in MM remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…21 Pathologically, malignant MM usually evolves from asymptomatic monoclonal gammopathy of underdetermined significance along with bone marrow microenvironment changes, genetic and cytogenetic abnormalities, which resulted in end-organ damage, renal insufficiency, anemia, elevated bone marrow angiogenesis, and osteolytic bone lesions. 3,22 Due to the genetic clonal heterogeneity of MM, treatment of patients remains as one of the main challenges. 6 Therefore, it is urgent to explore the biomarkers for disease development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple myeloma (MM), the second most common hematological malignancy, is characterized by abnormal proliferation of monoclonal plasma cells in bone marrow and overproduction of monoclonal immunoglobulin in serum and/or urine with an estimated 159 985 new cases and 106 105 deaths worldwide in 2018 1,2 . The typical symptoms of MM are bone pain, hypercalcemia, anemia, and renal insufficiency 3 . Over the last two decades, the introduction of immunomodulatory agents, proteasome inhibitors, monoclonal antibodies, and histone deacetylase inhibitor has improved the depth and duration of treatment responses and prolonged survival in patients with MM 4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression levels of several lncrnas have been reported in multiple myeloma (MM); their clinical significance, biological functions and potential molecular mechanisms in the disease have also been investigated (14)(15)(16). MM is the second most frequent hematological malignancy, and accounts for ~10% of all such malignancies (17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%